ENHANCING THE EFFECTIVENESS OF FORENSIC PSYCHIATRIC OPERATIONS FOR PREVENTING RECIDIVISM AMONG PSYCHIATRIC PATIENTS - Wankaew, Pattamaporn; Ninphet, Theeravut; Sripa, Kantita (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2025)
At present, the number of crimes committed by psychiatric patients is increasing, with many patients repeating offenses they have committed in the past. Enhancing the effectiveness of operations aimed at preventing recidivism is therefore critical in addressing this issue. This study aimed to examine the factors related to repeated offenses by psychiatric patients, investigate the operational context and obstacles in forensic psychiatric work within psychiatric hospitals, and explore strategies to improve the effectiveness of recidivism prevention. A qualitative research methodology was employed using in-depth interviews with 13 key informants, including multidisciplinary teams from psychiatric hospitals, police officers, and family members or caregivers. Data were analyzed using qualitative content analysis. The research findings revealed that repeated offenses were primarily associated with medication discontinuation, lack of continuity in treatment, insufficient caregiving skills among family members, and unsupportive social or environmental contexts. Forensic psychiatric services in hospitals cover both outpatient and inpatient care, focusing on patients’ safe reintegration into society. The main challenges include shortages of mental health professionals, the need for collaborative networks, and substance abuse that exacerbates psychiatric symptoms. Recommended preventive strategies include establishing forensic psychiatric units to prepare families, caregivers, neighbors, community leaders, and local networks, along with promoting positive attitudes and accurate understanding of mental health services among the public.